How Is the Consumer View? Concerning Perspectives in Ethics, Advertising Commitment on Attitude and Purchase Intention of Consumer - Utami, Budi (Jurnal Manajemen dan Inovasi (MANOVA), 2024)
The purpose of this study is to describe the picture of ethical commitment of advertising, advertisers, consumer buying attitudes and purchase intentions and the influence of academic service quality variables between advertising ethical commitments, advertisers partially and simultaneously on consumer buying attitudes and consumer buying interests. The population in this study was Management students of Majapahit Islamic University totaling 200 students and a sample of 6.8 students using proportional random sampling techniques. The scale used is the Likert scale. The type of measurement scale in this study is an ordinal scale that is converted into interval scale data through MSI (Method of Successive Interval). The results showed that the variables (1) Ethical commitment, (2) Advertising actors (endorsers), (3) Consumer buying attitudes, (4) Purchase intentions in good condition results. The calculation of the t test is known that: (1) there is a positive and significant influence between ethical commitment and consumer purchasing attitude, (2) there is a positive and insignificant influence between the role of advertising and consumer purchasing attitude, (3) there is a negative and insignificant influence between ethical commitment to consumer buying interest, (4) there is a negative and insignificant influence between advertisers on buying interest , (5) there is a positive and insignificant influence between consumer buying attitudes and buying interest.